On discreteness of spectrum of a second order differential operator - Sergey Labovskiy (Electronic Journal of Qualitative Theory of Differential Equations, 2020)
A new form of a necessary and sufficient conditions for the discreteness of the spectrum of singular operator $-\frac{1}{ρ(x)}(p(x)u')'$, $-∞\le a\le x\le b\le+∞$ is obtained. A simpler proof of the necessity is obtained.